2019
DOI: 10.1016/j.stem.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Activity of ETV5, RBPJ, and TCF3 Drives Formative Transition from Naive Pluripotency

Abstract: Summary The gene regulatory network (GRN) of naive mouse embryonic stem cells (ESCs) must be reconfigured to enable lineage commitment. TCF3 sanctions rewiring by suppressing components of the ESC transcription factor circuitry. However, TCF3 depletion only delays and does not prevent transition to formative pluripotency. Here, we delineate additional contributions of the ETS-family transcription factor ETV5 and the repressor RBPJ. In response to ERK signaling, ETV5 switches activity from supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
135
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 82 publications
(144 reference statements)
13
135
2
Order By: Relevance
“…Several KO cell lines showed lower baseline expression in 2i of Otx2, Fgf5, Dnmt3a/b and Pou3f1 (Oct6) ( Figure S2B). In line with recent results, we noted that depletion of several Fgf/ERK components resulted in reduced Dnmt3a/b, Pou3f1 and Fgf5 expression in 2i (Kalkan et al, 2019). Although Fgf/ERK signalling is effectively inhibited in 2i (Ying et al, 2008), our data suggest that either residual pathway activity or potential moonlighting functions of pathway components mediate poised expression of the formative pluripotency programme in 2i.Clustering based on the expression of ten naïve pluripotency marker genes showed that the downregulation of the naïve pluripotency TFs during formative differentiation is defective across multiple KOs (Figure 2A).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Several KO cell lines showed lower baseline expression in 2i of Otx2, Fgf5, Dnmt3a/b and Pou3f1 (Oct6) ( Figure S2B). In line with recent results, we noted that depletion of several Fgf/ERK components resulted in reduced Dnmt3a/b, Pou3f1 and Fgf5 expression in 2i (Kalkan et al, 2019). Although Fgf/ERK signalling is effectively inhibited in 2i (Ying et al, 2008), our data suggest that either residual pathway activity or potential moonlighting functions of pathway components mediate poised expression of the formative pluripotency programme in 2i.Clustering based on the expression of ten naïve pluripotency marker genes showed that the downregulation of the naïve pluripotency TFs during formative differentiation is defective across multiple KOs (Figure 2A).…”
supporting
confidence: 92%
“…This suggests that ESC differentiation requires coordinated activity changes of independent pathways under control of separable genetic networks. The observation that single gene depletion is not sufficient to eliminate exit from the naïve state is consistent with this interpretation (Kalkan et al, 2019). Our analyses exposed discrete pathway and GRN features that mediate timely and robust mammalian cell state transitions.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The first module displays high expression of core pluripotency genes ( Tbx3 , Klf4 , Nanog , and Esrrb ) that immediately drop in expression between B4 and N2, when cells enter the EpiLC stage. The second module is marked by genes that remain high in both naïve ES cells and EpiLCs, such as Pou5f1 , Tgif1 , Skil , and Etv5 , and which are often associated with early exit of pluripotency . Therefore, these genes only decrease in expression between N2 and N4.…”
Section: Resultsmentioning
confidence: 99%
“…The second module is marked by genes that remain high in both naïve ES cells and EpiLCs, such as Pou5f1, Tgif1, Skil, and Etv5, and which are often associated with early exit of pluripotency. 57,68,69 Therefore, these genes only decrease in expression between N2 and N4. A third module consists of genes such as Fgf5, Bmpr1a, Pou3f1, and Smad4, each showing a spike in expression only in the EpiLC stage and frequently linked to Smad mediated signaling.…”
Section: Identification Of Gene Co-expression Modules With Single-cmentioning
confidence: 98%